Steam whaling in the western Arctic / John R. Bockstoce, with contributions by William A. Baker and Charles F. Batchelder. - Bockstoce, John R. (Old Dartmouth Historical Society, 1977)
History of American whaling in the western arctic from 1880 to 1910. Includes ship design, ship biographies and a chronological list of wintering voyages 1850-1910.